Trace metals on anaerobic reactors treating domestic sewage - Silva, Julliana Alves [UNESP] (2021)
The use of anaerobic bioreactors for wastewater treatment depends on the adequate set-up and control of the physical, chemical, and biological parameters. In order to keep stable and suitable performance, it is essential to know the characteristics of the wastewater to be treated to choose the best treatment and reactor configuration, find the optimal hydraulic retention time (HRT), operational conditions and nutrients requirement. Regarding nutrients, deficiencies or excess of macro or micronutrients in anaerobic wastewater treatment systems are not a rare phenomenon. Knowing the wastewater composition and the biomass trace metals requirement in the system are necessary to achieve a maximal substrate conversion. Hence, providing a rational trace metal supplementation to the reactor. Therefore, in this thesis, the trace metal profile of domestic sewage (DS) treated in an innovative configuration of anaerobic reactor, the anaerobic structured-fixed bed reactor (ASTBR) is studied, together with the boundary conditions for stable operation, according to the organic matter load and trace metals contribution. In addition, a UASB reactor is operated in parallel as a model reactor to compare the ATBSR performance and as a source of sludge for the optimization of trace metals in DS anaerobic digestion, improving methane production. The results are presented in three individual papers, two published in international journals.